Concentração placentária dos peptídeos natriuréticos - ANP e BNP: associação entre a concentração placentária e os parâmetros clínicos maternos e fetais em gestações de normotensas e de hipertensas - Glaucia Aparecida de Menezes (2002)
Introduction: The study of concentration of the type A (ANP) and type B (BNP) natriuretic petptide in maternal circulation of patients with pre-eclampsia has been the focus of several publications. However, it remains unknown if it is possible to dose BNP in human placenta and what is the pathophysiological importance of ANP and BNP in the placenta of patients with pre-eclampsia. Objectives: To determine the presence and the concentration of ANP and BNP in the placenta andto study the influence of mother and fetus clinic factors on the placentalconcentration of these peptides. Methods: A prospective and transversal casecontrol study was performed, including 83 pregnant women, of which 27 were normotense and 56 were hypertense. Blood samples from the umbilical cord were drawn for gasometrical and placenta study for ANP and BNP dosage. Radioimmuneassay (RIA) was used to determine ANP and BNP and the results were given in pg/mg of soluble protein. Some variables from mother and fetus were studied and correlated with the concentration of peptides: age of mother, gestationage, arterial pressure, Doppler of the uterine artery, Doppler of the fetus, 1-minute and 5-minute Apgar score, neonates weight, pH and BE. Simple regression was used to study the correlations, while T-test was employed to compare peptide concentration averages in the study groups, with a significance level of 5% in hypothesis testing. Results: There was no difference in ANP and BNP concentration when comparing the normotense and hypertense groups (ANP: 0.881 ± 0.684 versus 0.859 ± 0.947 value-p=0.92; BNP: 17.4 ± 12.6 versus 21.9 ± 13.7 value-p=0.23). In the normotense group, ANP and BNP placentalconcentration showed no correlation with any mother-fetus factors studied. In the group of hypertense gestants, an increase of placental ANP concentration was observed in two subgroups: the subgroup having protodiastolic incisure in the uterine artery when compared to the Doppler without incisure (0.454 ± 0.392 versus 1.17 ± 1.16 value-p=0.022) and the subgroup of centralized fetus (1.16 ± 1.11 versus 0.408 ± 0.421 value-p=0.01). As to BNP, it was found an inverse association with gestation age and neonates weight (Value-p= 0.004 and value-p=0.001, respectively). Conclusions: No significant difference was found between the dosages of ANP and BNP in the normotense and hypertense groups, however, it was verified that some factors related to aggravation of maternal hypertense disease and compromising fetal vitality may influence the concentration of placental ANP and BNP peptides.